"Laços do saber [Knowledge laces]": a singular experience in the teaching of the technical qualification of the Community-based Health Agent (ACS), in the Peripheral area of the City of São Paulo, District of Capela do Socorro - Health Technical Supervision of Capela do Socorro - Durães-Pereira, Maria Beatriz Bendita Boldrin (Saúde e Sociedade, 2009)
This paper presents some perceptions of a teacher in her experience in the technical education of the ACS (Agente Comunitário de Saúde - Community-based Health Agent), Module I, developed at Unidades Básicas de Saúde (UBS - Basic Health Units). It reports the considerations of a Social Worker who was teaching in the classroom. The education of the class that is the object of this study was performed by two teachers in the classroom and five teachers at the UBS, being developed by means of 24 weekly meetings, each one lasting 8 hours, from April to November 2006, involving 21 students from 3 UBS: Gaivotas, Varginha, and Jordanópolis. The teaching-learning process took place with "successive approximations" to the personal, in-group, and theoretical contents, in which knowledge's "raw-material" flowed from the participants' exchange of experiences and life histories, and was concluded with a focal group for further research. On a weekly basis, after the evaluation, everyone expressed feelings regarding "what they had learned and what they were bringing home that day". Among the learned lessons, we can mention the enrichment of the building of "knowing how to be, how to do, and how to live together in the classroom" for the search of knowledge by the ACS. A paradigm was broken in "perceiving that nobody is prepared to teach; it is a challenging adventure, sculptured day by day in the learn-to-learn process". To conclude, it is important to encourage knowledge dissemination by means of a "conversation network", as recommended by Programa Saúde da Família (PSF - Family Health Program), involving all the participants in the health-disease process, thus favouring the ACS's contribution to disease prevention, health promotion and recovery in the community.